China's challenges - deLisle, Jacques, 1961-; Goldstein, Avery, 1954- (UPCC book collections on Project MUSE. Political Science and Policy Studies., 2015)
China today confronts challenges as daunting as any it has faced since the reform era began at the end of the 1970s. This book examines some of the most important and urgent of these social, political, economic, legal, and international challenges and prospects for addressing them under China's new leadership.